Male predominance in ketosis-prone diabetes mellitus - WANG, XIAOHAO (Biomed Rep, 2015)
The incidence of ketosis-prone diabetes mellitus (KPDM) shows a higher prevalence in men. The clear male predominance of this syndrome and its underlying pathogenesis mechanisms are unclear. KPDM, once described as atypical diabetes mellitus, idiopathetic type 1 diabetes (type 1B diabetes) and flatbush diabetes, is an uncommon form of diabetes characterized by severe reversible insulin deficiency. KPDM was first described and mostly observed in males of African-American descent and recently in Asian populations, including Japanese and Chinese. Patients with KPDM often present acutely with diabetic ketoacidosis without any immunological autoantibody to islet antigens of classic type 1 diabetes but demonstrate clinical and metabolic features of type 2 diabetes. Accumulating data indicated that gender-related body fat distribution, hormonal and genetic factors are associated with the diabetic process and the human glucose homeostasis and metabolism. A controversial question is whether and to what degree those factors contribute to the phenomenon of male predominance in KPDM. The present review focuses on the role of gender hormones and other potential precipitating factors in explaining the male predominance in KPDM patients.